2020
DOI: 10.1002/gps.5446
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic predictors of time to care home admission in people living with dementia in Wales: A routine data linkage study

Abstract: Objectives Limited research has shown that people with dementia (PwD) from lower socio‐economic backgrounds can face difficulties in accessing the right care at the right time. This study examined whether socio‐economic status (SES) and rural versus urban living location are associated with the time between diagnosis and care home admission in PwD living in Wales, UK. Methods/Design This study linked routine health data and an e‐cohort of PwD who have been admitted into a care home between 2000 and 2018 living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…1 ). Among the included studies, 10 were cross-sectional online surveys during the acute phase of the pandemic [ 33 42 ], five studies compared data collected prior with the data collected during the pandemic [ 43 47 ], two studies reported baseline data from ongoing longitudinal studies [ 48 , 49 ] and one study reported longitudinal data [ 50 ] (Table 1 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 ). Among the included studies, 10 were cross-sectional online surveys during the acute phase of the pandemic [ 33 42 ], five studies compared data collected prior with the data collected during the pandemic [ 43 47 ], two studies reported baseline data from ongoing longitudinal studies [ 48 , 49 ] and one study reported longitudinal data [ 50 ] (Table 1 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, two studies reported baseline data from ongoing longitudinal studies in the United Kingdom. The first one, an ongoing online and telephone survey, reported that only a few older adults showed clinically significant depressive and anxiety symptoms (5%), assessed by PHQ-9 and GAD-7, respectively [ 48 ]. The second was the baseline survey of the ongoing CHARIOT COVID-19 Rapid Response Study (CCRR), conducted within six weeks of lockdown in London.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wider community testing was negligible in the early parts of our analysis period [25] and likely differed by local authority capacity which would bias results if included. Furthermore, staff, healthcare professionals and any other individuals entering the care homes are not necessarily from or have only interacted with the immediate local areas [26], so fully capturing this would require location data for multiple individuals over time. Good-quality data on local policy responses was also unavailable.…”
Section: Strengths and Limitationsmentioning
confidence: 99%